HOW SHOULD TRANSLATION COMPETENCE BE TAUGHT: A QUEST FOR A BETTER APPROACH IN TRANSLATION CLASS - Condro Nur Alim (University of Muhammadiyah Purwokerto, 2015)
It is widely agreed that the main aim of translation education is to develop students’ translation competence, therefore most researches in translation education contexts focus on identifying the components of transla-tion competence and appropriate curriculum models that integrate these components with suitable teaching strategies. Since translation competence consists of many sub-competences, developing these sub-competences therefore should be the main consideration in translation education. This article is aimed at discussing translation competence in general and how this competence should be de-veloped in a translation class context. Understanding these sort of things is important in formulating the best approach in translation teaching and learning in order to avoid the possible overlap between ‘translation teaching’ and ‘language teaching’, due to the fact that in some cases what the students get in translation class is not ‘how to be a good translator’ but ‘how to be a good language learner’. Further, understanding the nature of students’ translation competence and how this should be developed can give an important conceptual framework in formulating a better translation curriculum which considers all aspects the students need to build their translation competence. Keywords: students, translation, competence, teaching.